Near‐Equilibrium Growth of Chemically Stable Covalent Organic Framework/Graphene Oxide Hybrid Materials for the Hydrogen Evolution Reaction. Issue 2 (22nd November 2021) - Bai, Yichao; Liu, Youxing; Liu, Minghui; Wang, Xinyu; Shang, Shengcong; Gao, Wenqiang; Du, Changsheng; Qiao, Yan; Chen, Jianyi; Dong, Jichen; Liu, Yunqi
Abstract: Facile synthesis and post‐processing of covalent organic frameworks (COFs) under mild synthetic conditions are highly sought after and important for widespread utilizations in catalysis and energy storage. Here we report the synthesis of the chemically stable aza‐fused COFs BPT‐COF and PT‐COF by a liquid‐phase method. The process involves the spontaneous polycondensation of vicinal diamines and vicinal diketones, and is driven by the near‐equilibrium growth of COF domains at a very low monomer concentration. The method permits in situ assembly of COFs and COF‐GO hybrid materials and leads to the formation of a uniform conducting film on arbitrary substrates on vacuum filtration. When used as electrocatalysts, the as‐prepared membranes show a fast hydrogen evolution reaction (HER) with a low overpotential (45 mV at 10 mA cm −2 ) and a small Tafel slope (53 mV dec −1 ), which are the best among metal‐free catalysts. Our results may open a new route towards the preparation of highly π‐conjugated COFs for multifunctional applications. Abstract : A liquid‐phase method has been developed for the synthesis of highly conjugated covalent organic frameworks (COFs). Vacuum filtration leads to the formation of a uniform conducting film of the COFs and COF‐GO hybrid materials on a variety of substrates. The overpotential of one of the materials was as low as 45 mV in 0.5 m H2 SO4 and reached a current density of 10 mA cm −2, which is better than all the metal‐free catalysts currently available.